Ergonomic workstation design for science laboratory / Norhafizah Rosman … [et al.] - Rosman, Norhafizah; Daruis, Dian Darina Indah; Ahmad, Nurrohana; Kusin, Mazlin (2013)
The purpose of this study was to observe the anthropometric data collected compared to the existing data. Data were determined to propose the new design of chair/stool and workbench for science laboratory. The data collection samples were conducted at Universiti Teknologi MARA, Kampus Khazanah Alam, Pahang and the samples among the students in college. The ranges of ages of the samples were around 18 and above years old among the student in college who volunteer to be physically measured in this study. The sample involved 30 male students and 30 female students. Thirteen human body dimensions were measure: stature, shoulder breadth, chest depth, sitting height, sitting eye height, sitting shoulder height, popliteal height, sitting knee height. forearm hand length, sitting elbow height. thigh clearance. head length and hip breadth. Finally, the anthropometric data were compared to the previous study. The finding showed the similarity with the existing data. It proves 90% achieved the human satisfaction, example is height between 1198. 78mm and 1899.91mm (show the normal distribution). Male students show the higher average value compared to females for stature, sitting height and sitting eye height. There were also mismatches between measurement of existing furniture with the anthropometry data based on seat height and seat area. Based on the data analysis. stool/chair and workbench were designed with the adjustment of the height for seat. The purpose is to give satisfaction to majority of the students.